DEVELOPMENT AND TESTING OF A WEB-ORIENTED ELECTRONIC DOCUMENT MANAGEMENT SYSTEM USING BLOCKCHAIN TECHNOLOGIES ELEMENTS - PIROH, OLEKSANDR; HOLOVNIA, OLENA; KOLOSHCHUK, MARIIA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article examines possible ways to solve bureaucratic and corruption problems in state organizations with the help of blockchain technologies, analyzes the web services currently used for document management and reveals that there are many offers of online document management systems in the corporate upper price segment, even using blockchain technologies. In the lower price segment, document protection offers are possible either for an additional price or with the use of third-party tools, connected or developed independently. Threat model analysis showed that the main offenders are an insider who has access to the administration of the document registration application or to the administration of the application database, which carries the threat of changing this data, and an external offender who can use the main web applications vulnerabilities, such as SQL injection, CSRF, XSS attacks, brute force attacks, for reconnaissance, obtaining administrative access and making changes to registration data. The application has been developed and tested that implements certain protection mechanisms: Use of blockchain technology for the impossibility of imperceptibly changing the registration data of registered documents; of Registered documents hash sum storage and registered documents verification; Setting up delimitation of access to preserve confidential and commercial secrets in the institution; Protection against other web application vulnerabilities. It has been established that interest in blockchain technologies continues to grow with the reform and development of all spheres of the Ukrainian state, namely medical reform, judicial and law enforcement reform, the development of the electronic state and the so-called "digitalization" of the state, and in the context of the ongoing cyber war with the aggressor state. The use of blockchain technology can solve many problems related to bureaucracy, corruption, theft and fraud. Therefore, the application of blockchain logic in electronic document management systems reliably prevents attempts by criminals to change registered documents.